Diet-induced Obesity Differentially Modulates Cardiac Inflammatory Status in the C57 and FVB Mouse Strains - Gaisler-Silva, Fernanda; Junho, Carolina V. C.; Fredo-da-Costa, Izabelle; Christoffolete, Marcelo A.; Carneiro-Ramos, Marcela Sorelli (Current Molecular Medicine, 2022)
Background: Cardiovascular diseases correspond to the highest risk of sudden death worldwide, and obesity is largely related to be an increased risk factor. There is a higher prevalence of arterial hypertension in obese individuals, including the presence of cardiac hypertrophy. It is already known the role of toll-like receptors [TLR], mainly 2 and 4 in heart cells, as fundamental to the process of cardiac hypertrophy. Obesity has been studied as an activator of damage-associated molecular patterns [DAMPs], which use the TLR signaling pathway to increase the nuclear factor of inflammation, NF-kB, increasing cytokine expression in heart tissue. It’s already known that FVB/N and C57BL/6 mouse strains have different behaviors in relation to metabolism, but the difference in cardiac tropism and innate immune system modulation are not clear. Methods: The present study aimed to evaluate the contribution of innate immune factors to cardiac hypertrophy induced by an experimental model of obesity comparing two mouse strains: C57BL/6 and FVB/N. Both strains were submitted to a high-fat diet containing 23% protein, 35.5% carbohydrate, and 35.9% fat for 68 days. Hearts were collected, weighed, and submitted to RT-qPCR, and the serum was analyzed by Bioplex. Results: We observed an increase in heart mass after 68 days in both strains. This was followed by an increase of α-actin only in C57BL/6 while ANF was increased in FVB/N. Gene expression of innate immune components and inflammatory cytokines were only increased in C57BL/6, but not in FVB/N. Conclusion: Based on the results obtained, we verified that C57BL/6 mice had a more robust action of innate immune system then FVB/N.
Keywords: TLR